Patients' acceptability and implementation outcomes of a case management approach to encourage participation in colorectal cancer screening for people with schizophrenia: a qualitative secondary analysis of a mixed-method randomised clinical trial. Issue 6 (14th June 2022) - Yamada, Yuto; Fujiwara, Masaki; Shimazu, Taichi; Etoh, Tsuyoshi; Kodama, Masafumi; So, Ryuhei; Matsushita, Takanori; Yoshimura, Yusaku; Horii, Shigeo; Fujimori, Maiko; Takahashi, Hirokazu; Nakaya, Naoki; et al.
Abstract : Objectives: We examined the efficacy of case management (CM) interventions to encourage participation in colorectal cancer screening for patients with schizophrenia. This study aimed to clarify patients' acceptability of the intervention and the helpful components of the intervention. Simultaneously, the study aimed to determine the acceptability, appropriateness and feasibility of the intervention from the perspective of psychiatric care providers. Study design and setting: This study was a secondary qualitative analysis of a mixed-method randomised controlled trial that evaluated the efficacy of the CM approach to encourage participation in cancer screening for people with schizophrenia. The intervention comprised education and patient navigation for colorectal cancer screening. Interviews were conducted with patients who received the intervention and staff from two psychiatric hospitals in Japan who delivered the intervention. Participants: Of the 172 patients with schizophrenia who participated in the trial, 153 were included. In addition, three out of six providers were included. Data collection and analysis: Using a structured interview, the case manager asked participants about patient acceptability and the helpful components of the intervention. Content analysis was conducted for the responses obtained, and the number of responses was tabulated by two researchers. For the interviews with the providers, opinions obtained from verbatim transcripts were extracted and summarised. Results: Forty-three of the 56 patients perceived that the intervention was acceptable. For the intervention component, inperson counselling with an explanation of the screening process by psychiatric care providers was most frequently reported by the patients as helpful (48 of the 68 respondents). Psychiatric care providers evaluated the intervention as acceptable, appropriate and easy to understand and administer. However, providing the intervention to all patients simultaneously was considered difficult with the current human resources. Conclusions: This study showed that the CM intervention was perceived as acceptable by patients and acceptable and appropriate by psychiatric care providers. Trial registration number: UMIN000036017.